Meaning Shift on Indonesian Economic Terminologies Borrowed From English - Kumaladewi, Intan Ratih (LANTERN (Journal on English Language, Culture and Literature), 2016)
Vocabulary development is intended to express an object that does not have a suitable expression as the object reference. It can be done through borrowing words from another language. In mass media such as newspaper, words borrowing are common to use. Often, these borrowed words experience meaning shift in the process. The purpose of this research is to find the meaning shifts that occurin Indonesian economics terminologies borrowed from English which are obtained from the Economy Rubric of Kompas daily newspaper. I use analytical or referential approach and lexical meaning to find the meaning of Indonesian economic terminologies borrowed from English and its meaning components. The research is considered as a qualitative and descriptive research. IutilizePadan method involving referential and translational approaches.There are three types of meaning shift appear in the Economic Rubric of Kompasdaily newspaper, namely widening, narrowing, and total change. I also find meaning shift factors existing in the Economic Rubric of KompasDaily Newspaper, namely linguistic causes, historical causes, social causes and the needs of new meaning.